2017
DOI: 10.1039/c6gc03528k
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient aqueous phase chemoselective hydrogenation of α,β-unsaturated aldehydes catalysed by phosphine-decorated polymer immobilized IL-stabilized PdNPs

Abstract: An aqueous phase hydrogenation of α,β-unsaturated aldehydes with remarkable selectivity for the CC double bond under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 76 publications
1
36
0
Order By: Relevance
“…Pd-NPss urrounded by variousm atricest oi mproveb oth stability and solubility are currently of high interest as catalysts for organic synthesis, as the possibility of using water as as olvent provides the opportunity for them to be used in green chemistry. [14] Pd-NPs of an average size of 2.1 nm and stabilized by an 2,2'-bipyridine-functionalized polyethylene glycol monomethyl ether (PEG-OMe) matrix (Pd@BiPy-PEG-OMe) (1), as shown in Figure 1, with aP dc ontent of 2.0 wt %h ave been synthesized, characterized and employed for the catalytic hydrogenation of variousn itrilest oa mides in water. [15] Herein 1 has been used to photocatalytically generateh ydrogen, followingt he proposed catalytic cycles depicted in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Pd-NPss urrounded by variousm atricest oi mproveb oth stability and solubility are currently of high interest as catalysts for organic synthesis, as the possibility of using water as as olvent provides the opportunity for them to be used in green chemistry. [14] Pd-NPs of an average size of 2.1 nm and stabilized by an 2,2'-bipyridine-functionalized polyethylene glycol monomethyl ether (PEG-OMe) matrix (Pd@BiPy-PEG-OMe) (1), as shown in Figure 1, with aP dc ontent of 2.0 wt %h ave been synthesized, characterized and employed for the catalytic hydrogenation of variousn itrilest oa mides in water. [15] Herein 1 has been used to photocatalytically generateh ydrogen, followingt he proposed catalytic cycles depicted in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…38 Polymer immobilized ionic liquids 1a and 1b were prepared by AIBN-initiated radical polymerization of the constituent imidazoliummodified monomer or its PEGylated counterpart with cation appropriate cross-linker and 4diphenylphosphinostyrene in the desired ratio. [23][24][25] Both polymers were impregnated by exchanging half of the halide anions with [AuCl4]to afford the corresponding tetrachloroaurateloaded precursors 2a ([AuCl4]Cl@PPh2-PIILP) and 2a.PEG ([AuCl4]Br@PPh2-PEGPIILP) which have a gold to phosphine stoichiometry of one; full characterization details are provided in the ESI. As we have previously demonstrated that palladium nanoparticle-based catalysts generated in situ by reduction of the corresponding tetrachloropalladate-loaded precursor immediately prior to use are as efficient as their ex situ prepared counterparts, precursors, 24-25 2a and 2a.PEG were used for catalyst evaluation and optimization while samples of 3a and 3a.PEG were generated under conditions of catalysis to obtain TEM and XPS characterization data on the active species.…”
Section: Synthesis and Characterization Of Phosphine-modified Gold Prmentioning
confidence: 99%
“…21 While heteroatom donors were initially incorporated into ionic liquids to stabilize NPs with respect to agglomeration under conditions of catalysis, 22 it is now clear that these donors could also enable the surface electronic structure to be modified and/or NP size and morphology to be controlled and, in this regard, HAD-PIILs may well prove to be tunable multifunctional supports for developing more efficient catalysts and processes. 14c,7a,15a,15d,22p Gratifyingly, our initial foray in this area has proven extremely promising as PEG-modified phosphine-decorated polymer-immobilized ionic liquid-stabilized palladium nanoparticles were shown to be remarkably active and selective catalysts for hydrogenation of -unsaturated aldehydes, ketones and nitriles, 23 hydrogenation and transfer hydrogenation of nitroarenes in water 24 and Suzuki-Miyaura cross-couplings in aqueous media. 25 With the aim of further exploring the concept of PIIL stabilized NPs we have recently extended our study to include gold nanoparticle-based systems in order to undertake a comparative study of their efficacy as catalysts for the reduction of nitroarenes.…”
Section: Introductionmentioning
confidence: 99%
“…Supported metal nanoparticles as an important class of catalysts are versatile substrates in organic synthesis . Palladium nanoparticles (Pd NPs) because of their attractive chemical and physical properties have been broadly used in the fields of coating, fuel cells, electronics, as well as catalysis . The utilization of Pd NPs in catalysis systems involves some difficulty such as agglomeration, due to their high surface energy, and problems of separation from the reaction medium which is due to their homogeneous character.…”
Section: Introductionmentioning
confidence: 99%